Factors associated with utilization of cervical cancer screening services among HIV-positive women aged 18 to 49 years at Lira regional referral hospital, Northern Uganda - Layet, Florence; Murungi, Tom; Ashaba, Nasser; Kigongo, Eustes; Opollo, Marc Sam (BioMed Central Ltd, 2024)
Abstract Background Women with HIV have a higher risk of getting cervical cancer due to induced immunosuppression. Though this burden could be avoided through early identification and appropriate management, there is a paucity of information about the utilization of cervical cancer screening (CCS) services in Lira City, Uganda. This study investigated the level and factors associated with the utilization of cervical cancer screening services among HIVpositive women aged 18 to 49 years at Lira Regional Referral Hospital, Lira City, Uganda. Methods We conducted a facility-based cross-sectional study employing quantitative techniques. We used consecutive sampling to recruit 297 HIV-positive women at the ART clinic of Lira Regional Referral Hospital. A structured researcher-administered questionnaire was used to collect data. Descriptive statistics were performed to summarize the data. A modified Poisson regression using robust standard errors was performed to ascertain the factors associated with the utilization of cervical cancer screening. Prevalence ratios at 95% confidence intervals were reported. Results Out of 297 respondents, 175(58.9%) utilized cervical cancer screening in this study. The factors found to be associated with CCS were; having ever heard of CCS (Adjusted Prevalence Ratio [PR] 1.80, 95% CI 1.31–2.49, p<0.001), knowing where CCS is done (Adjusted PR 1.99, 95% CI 1.42–2.81, p<0.001), fear of CCS outcomes (Adjusted PR 0.67, 95% CI 0.54–0.84,p<0.001), not knowing whether CCS is beneficial or not (Adjusted PR 0.39, 95% CI 0.20– 0.75,p=0.005) and having friends/relatives who screened for cervical cancer (Adjusted PR 1.31, 95% CI 1.09–1.59, p=0.005). Conclusion The level of utilization of cervical cancer screening services among HIV-positive women was suboptimal. Implementation of structured interventions aimed at improving cervical cancer screening awareness among HIVpositive women is crucial. Additionally, to increase opportunities for screening and knowledge on cervical cancer prevention, screening programs can target HIV-positive women during their routine clinic visits.
Keywords: Cervical Cancer, Cancer Screening, HIV, Factors, Utilization